2014
DOI: 10.17795/jjnpp-15913
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Removal From Aqueous Solutions With Chitosan-Coated Magnetite Nanoparticles Optimized Using the Box-Behnken Design

Abstract: Background: Nowadays, removal of heavy metals from the environment is an important problem due to their toxicity. Objectives: In this study, a modified method was used to synthesize chitosan-coated magnetite nanoparticles (CCMN) to be used as a low cost and nontoxic adsorbent. CCMN was then employed to remove Hg 2+ from water solutions. Materials and Methods: To remove the highest percentage of mercury ions, the Box-Behnken model of response surface methodology (RSM) was applied to simultaneously optimize all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…It has also been reported that at pH 5-6, the presence of the amino group in CHT (pK a ¼ 6.5) becomes protonated, and H + ions are produced in the presence of HCl, which leads to formation of anion complexes such as HgCl 3 À1 . This anion is adsorbed on Ce-PVA-CHT composite nanobers 18,47 by a complex formation with amino and Ce present in composite nanobers. No signicant change in the pH value of the solution before and aer Hg(II) adsorption was observed.…”
Section: Inuence Of Ph Dosage and Ce Content On Hg(ii) Adsorptionmentioning
confidence: 99%
“…It has also been reported that at pH 5-6, the presence of the amino group in CHT (pK a ¼ 6.5) becomes protonated, and H + ions are produced in the presence of HCl, which leads to formation of anion complexes such as HgCl 3 À1 . This anion is adsorbed on Ce-PVA-CHT composite nanobers 18,47 by a complex formation with amino and Ce present in composite nanobers. No signicant change in the pH value of the solution before and aer Hg(II) adsorption was observed.…”
Section: Inuence Of Ph Dosage and Ce Content On Hg(ii) Adsorptionmentioning
confidence: 99%
“…In an endeavour to overcome the problems, recent research has been shifted to preparing magnetic adsorbents by inducing magnetic particles [18][19][20][21][22]. Magnetic adsorbents have been reported to have high surface/volume ratios, chemical stability, biocompatibility, and excellent magnetic properties and can be easily separated from the aqueous solution by using an external magnetic field [23]. The unique properties of magnetic induced adsorbents provide a plethora of ideas to solve problems in adsorption technology.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, scale-up of the process is difficult since it requires a number of experiments to get the optimum levels thereby resulting in a costly process [24]. All the process independent variables can be optimized collectively by applying a response surface methodology (RSM), a mathematical statistical technique which optimizes the process and evaluates the relationship between a set of independent variables [18,[23][24][25][26]. Moreover, it evaluates the relative significance of the various independent variables even in the presence of complex factorfactor interactions [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the Freundlich isotherm describes the metal adsorption in a heterogeneous system and is not restricted to the monolayer formation (Rahbar et al . ). The linear graphs of the Langmuir and Freundlich isotherms were plotted for each ion and the parameters of adsorption isotherms are shown in Table (Supporting Information Figs S4 and S5).…”
Section: Resultsmentioning
confidence: 97%